Development of Copper Hatch Baskets and Evaluation of the Productive Indexes of a Commercial Hatchery - Depner, Ronise Faria Rohde; Lucca, Vivian; Depner, Rômulo Alexandre; Pontin, Karine Patrin; Pötter, Luciana; Borges, Karen Apellanis; Furian, Thales Quedi; do Nascimento, Vladimir Pinheiro; Lovato, Maristela (Acta Scientiae Veterinariae, 2020)
Background: The dissemination of pathogenic microorganisms in hatcheries leads to a higher number of contaminated eggs, causing reduction in hatchability and increase of discarded chicks. Sanitation programs are crucial for maximum hatchability and chick quality. Efforts have been made to find alternative approaches to the conventional disinfectants, and surfaces with copper, which have antimicrobial properties, could assist in this process. However, the possible adverse effects of copper surfaces on chicks in hatcheries have not yet been evaluated. The present study aimed at developing hatch baskets composed of copper and evaluating the effect of these baskets on the productive indexes of a hatchery. Materials, Methods and Results: For this experiment, 3.15 kg hatch tray prototypes with 99.9% Cu (Cu11000) were developed to fit inside conventional polypropylene hatch baskets (580 × 755 × 83 mm). Six polypropylene hatch baskets (control group) and 6 polypropylene hatch baskets covered by 99.9% copper (Cu11000) hatch trays (test group) were evaluated during 5 hatchings. Hatched eggs and chicks remained in contact with the hatch basket surfaces for at least 72 h, corresponding to the entire period in which they were located in the hatcher. Cleaning and disinfection programs of the hatchery were not modified. The level of microbial contamination on the hatch baskets was evaluated at 6 different periods: 0 h (initial contamination after disinfection and egg transfer to the trays); 24 h, 30 h, 45 h and 60 h after the first sampling; and at the moment when chicks were removed from the hatching cabinet and transferred to the chick-holding room (> 60 h). Counting of total moulds and yeasts, mesophilic microorganisms, Enterobacteria and Escherichia coli colonies was performed. The number of hatched chicks, non-hatched eggs, and chicks discarded were registered for each hatching. Microbiologic analyses showed no growth on hatch baskets neither of the test group nor on those of the control group, regardless of the period evaluated. No significant difference was found between the two groups in the counts of hatched chicks, non-hatched eggs, and chicks discarded. Discussion: The antimicrobial efficacy of copper surfaces has been established for a variety of bacteria and fungi, including in the healthcare environment. In addition, antimicrobial resistance to copper is extremely rare because of copper’s multisite kill mechanism and other mostly nonspecific damage mechanisms. Several copper applications have been established; however, the potential adverse effects of using copper surfaces in hatcheries on chicks or on hatchery productive indexes had not yet been evaluated. The analyses performed in this study did not show microbiological growth. The results showed that the copper surface did not cause any significant adverse effects on chicks. The hatched chicks were visually healthy, and no significant difference was found between the numbers of chicks discarded in the control and test groups. Since the production parameters were not altered or impaired in the present study, it is possible to conclude that the use of copper surfaces in hatcheries can be an effective tool in the microbiological control of these environments. Nevertheless, copper alloys lend themselves to the creation of self-sanitizing surfaces that should be used as a complement and not as a substitute for standard cleaning and disinfection practices.